Two new species of Sclerothyone from the southwestern Atlantic Ocean, with a key to genera and species of Sclerothyoninae (Holothuroidea: Dendrochirotida: Sclerodactylidae) - Martins, Luciana; Tavares, Marcos (Zootaxa, 2019)
Sclerothyone Thandar, 1989, currently restricted to two South African species, is here expanded to include two new species from off coast of Brazil. These new species expand the distribution of the genus to the southwestern Atlantic Ocean. Sclerothyone reichi sp. nov. is characterized by having body wall with multilocular two pillared tables with multiperforate disc and short spire, ending in a narrow crown of teeth; tentacles with rods and introvert with two pillared tables and rosettes; tube feet with only end plates. Sclerothyone oloughlini sp. nov. is distinctive in having a body wall with multilocular, two pillared tables; handles present and multilocular two-pillared tables; circular disc without handle; and plates (near the anus). The new species resemble each other in the tentacles with rods. However, Sclerothyone oloughlini sp. nov. stands apart from S. reichi sp. nov. in the introvert with rosettes; tube feet with two pillared supporting tables, arched plates and end plates. The possible assignment of Cucumaria nozawai Mitsukuri, 1912 and Thyone adinopoda Pawson & Miller, 1981 to Sclerothyone, and the position of Thyone neofusus Deichmann, 1941 in Temparena Thandar, 1989, are briefly discussed. A key to all genera and species of Sclerodactylinae is provided.